Halloysite Nanotube-Reinforced Ion-Incorporated Hydroxyapatite-Chitosan Composite Coating on Ti-6Al-4 V Alloy for Implant Application - Manickam Chozhanathmisra; Kannaiyan Pandian; Dharman Govindaraj; Palanisamy Karthikeyan; Liviu Mitu; Rangappan Rajavel (Journal of Chemistry)
To develop the corrosion resistance and improve the biological performance of a titanium implant (Ti6Al4V alloy), a series of mineral (M = Zn and Mg)-substituted hydroxyapatite (MHA), chitosan-MHA (CS-MHA), halloysite nanotube-MHA (HNT-MHA), and HNT-CS-MHA composite coatings were fabricated on the anodized titanium alloy by electrodeposition. The surface morphology and cross section of various coated composites were investigated by high-resolution scanning electron microscopy (HR-SEM). Furthermore, the functional groups and phase structure of the composite coatings were investigated by Fourier transform infrared spectroscopy (FTIR) and X-ray diffractometry (XRD). Corrosion behaviors of the composite coatings were also investigated by polarization and impedance spectroscopy (EIS). Moreover, the cell-material interaction of the composite coating was observed in vitro with human osteoblast MG63 cells for cell proliferation at 1, 4, and 7 days of incubation. Consequently, HNT-CS-MHA-Ti may have potential applications in the field of orthopedic and dental implants.